A BRIEF HISTORY OF THE NOTIONS ”CONSONANCE” AND “DISSONANCE” - Lucia Cristina MĂNIUŢ (Studia Universitatis Babeş-Bolyai. Musica)
From a historical point of view, the phenomenon called consonance/dissonance has been perceived under three main trends: the first one – mathematical; the second one – acoustical and psychological and the third one – contextual. My research is based on Plato’s thought that consonants are produced by planets as well, in their movement on the orbits, a thought that is to be found in the sxteenth century as well in Zarlino’s Instituzioni harmoniche.